Precious Forests Precious Earth - Zlatic, Miodrag (IntechOpen, 2015)
Forests are the dominant terrestrial ecosystem of Earth. They are distributed across the globe. Forests account for 75% of the gross primary productivity of the Earth's biosphere, and contain 80% of the Earth's plant biomass. Human society and forests influence each other in both positive and negative ways. Forests provide ecosystem services to humans. Forests can also impose costs, affect people's health, and interfere with tourist enjoyment. This publication presents reviews and research results on negative and positive human interference on forests, as well as ecology, management, governance, policy and economic issues. The book consists of four sections with 12 chapters derived from around the world.